Service deployment and scheduling for improving performance of composite cloud services. (March 2019) - Lu, Yu-Chun; Lin, Chih-Kai; Lai, Kuan-Chou; Tsai, Meng-Han; Wu, Ying-Jhih; Chang, Hsi-Ya; Huang, Kuo-Chan
Abstract: Cloud computing and services have greatly changed the way how people develop and use software, and also raised a lot of new research issues. In this paper, we investigate two such important issues, service deployment and service request scheduling, for composite cloud services in dynamic cloud environments. We present load-aware service deployment approaches for dynamic workload and a service request scheduling method based on task ranking mechanisms. The proposed approaches can effectively improve the execution performance of composite cloud services in dynamic cloud environments. A series of simulation experiments have been conducted to evaluate the proposed approaches. The experimental results show that our approaches outperform previous methods significantly in terms of average service response time.